The effect of the Xpert MTB/RIF test on the time to MDR-TB treatment initiation in a rural setting: a cohort study in South Africa's Eastern Cape Province. Issue 1 (December 2017) - Iruedo, Joshua; O'Mahony, Don; Mabunda, Sikhumbuzo; Wright, Graham; Cawe, Busisiwe
Abstract Background There are significant delays in initiation of multidrug-resistant tuberculosis (MDR –TB) treatment. The Xpert MTB/RIF test has been shown to reduce the time to diagnosis and treatment of MDR-TB predominantly in urban centres. This study describes the time to treatment of MDR-TB and the effect of Xpert MTB/RIF on time to treatment in a deprived rural area in South Africa. Methods This was a retrospective cohort study analysing the medical records of patients diagnosed with MDR-TB in King Sabata Dalindyebo Sub-District between 2009 and 2014. Numerical data were reported using the Kruskal-Wallis and Wilcoxon sum rank tests and categorical data compared using the two-sample test of proportions. Results Of the 342 patients with MDR-TB identified, 285 were eligible for analysis, of whom 145 (61.4%) were HIV positive. The median time from sputum collection to MDR-TB diagnosis was 27 days (IQR: 2–45) and differed significantly between diagnostic modalities: Xpert MTB/RIF, 1 day (IQR: 1–4;n  = 114:p  < 0.0001); Line Probe Assay 12 days (IQR: 8–21;n  = 28;p  < 0.0001); and culture/phenotypic drug sensitivity testing 45 days (IQR: 39–59;n  = 143:p  < 0.0001). The time from diagnosis to treatment initiation was 14 days (IQR: 8–27) and did not differ significantly between diagnostic modality. The median time from sputum collection to treatment initiation was 49 days (IQR: 20–69) but differed significantly between diagnostic modalities: Xpert MTB/RIF, 18 days (IQR: 11–27;n  = 114;p  < 0.0001); Line Probe Assay 29 days (IQR: 14.5–53;n  = 28;p  < 0.0001); and culture/phenotypic drug sensitivity, 64 days (IQR: 50–103;n  = 143:P  < 0.0001). Age, sex and HIV status did not influence the time intervals. Conclusions Xpert MTB/RIF significantly reduced the time to MDR-TB treatment in a deprived rural setting as a result of a reduced time to diagnosis. However, the national target of five days was not achieved. Further research is needed to explore and address programmatic and patient-related challenges contributing to delayed treatment initiation.